4 - Accessibilité de l’information en Afrique - Alain Kiyindou, (Africa Media Review, 2008)
This paper aims at a critical assessment of the so-called information society. In actual fact, information is central to society in that it is involved in every process of change. For the user of information, what matters most is not the amount of resources invested, but the results or user- handy information. It is at this juncture that accessibility becomes a concern; that is “the possibility for the public to choose the programmes that suit their needs and to be able to express those needs”. However, another important dimension to accessibility is the possibility users have of putting the acquired knowledge into effective use. In the era of New Information and Communication Technologies, the concept of accessibility stretches beyond mere connectivity to include issues relating to durability.